The Diversity Of Macrozoobenthos On The Coastal Areas Of Batu Bara Regency - Gilang Pradana , Tengku; Adha Putra, Chairunas; Mustaqim, Mustaqim; Hafzari, Rini; Mukra, Rizal; Silaban, Friends; Muammar, Muammar (Universitas Negeri Medan, 2024)
Research of the diversity macrozoobenthos in Batu Bara Regency is crucial to identify the current condition of coastal ecosystems. This information can provide an overview of water quality, resource sustainability status, and serve as a basis for better planning and management of coastal areas. This research is also expected to serve as a reference for developing strategies to mitigate the negative impacts of human activities on coastal ecosystems, ensuring the balance of ecosystems and the preservation of biodiversity. This research will be analyze diversity and abundance (ind/ha) of macrozoobenthos, ecological index data and physical environmental factors and substrate characteristics. The diversity of macrozoobenthos at Sujono Beach, Sejarah Beach, and Kresek Beach consists of three phyla, six classes, and 28 species. The abundance of macrozoobenthos at Sujono Beach is 2459 ind/m3, at Sejarah Beach is 1525 ind/m3, and at Kresek Beach is 1218 ind/m3. The species richness index, diversity index, and evenness index of macrozoobenthos at all three beaches fall into the moderate category, while in the dominance index, none of the beaches have dominating species. The substrate characteristics at Sujono Beach have a sandy clay texture, while at Sejarah Beach and Kresek Beach, they have a dusty clay texture.